The importance of dynamic capabilities in the reformulation of an innovative competitive advantage. Case study of Cordoba technology companies - Trillo-Holgado, María Amalia; León-Urban, Carolina; López-Caballero, Rocío (Revista de Estudios Andaluces, 2022)
The innovation capacity of companies is related to the reconfiguration or modification of their competitive advantages. It is best explained from the perspective of dynamic capabilities (organisational abilities to manage their resources in changing environments), a field that requires further practical study. Methodologically, a model is provided. The model identifies the most important variables and indicators in order to facilitate managers strategy. That model allows them to explain how those resources and capacities taking part in the development of new processes, products or services influence the reconfiguration of competitive advantage. To support the utility of the model, an exemplary case carried out within the technology sector based on a public and a private company. As conclusions and results, it can be stated that this empirical study supports the scientific literature, verifying how specific innovation activities have to do with the dynamic capabilities from which the company’s sustainable competitive advantage is determined. Regarding that, culture and collaborative behavior play a fundamental role, which along with technology, are evident in the case of the private sector compared to the public one.